2022
DOI: 10.1021/jacs.2c07934
|View full text |Cite
|
Sign up to set email alerts
|

Ring Contraction of a Tungstacyclopentane Supported on Silica: Direct Conversion of Ethylene to Propylene

Abstract: The reaction of W­(NAr)­(13C4H8)­(OSiPh3)2 (1) (NAr = 2,6-diisopropylphenylimido) with silica partially dehydroxylated at 700 °C (SiO2‑700) is highly dependent on the reaction conditions. The primary product of this reaction is W­(NAr)­(13C4H8)­(OSiPh3)­(OSi­(O−)3) (2) when the reaction is carried out in the dark. Grafting 1 onto SiO2‑700 in ambient lab light results in the formation of 2, W­(NAr)­(13CH2 13CH2)­(OSiPh3)­(OSi­(O−)3) (4), and one isomer of square-pyramidal W­(NAr)­(13CH2 13CH­(13Me)13CH2)­(OSiPh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…This work raises the question as to whether nonaryl-substituted terminal olefins behave similarly in terms of protonation or whether styrene is a special case. In terms of the larger picture concerning the formation of alkylidene complexes from olefins, it has to be noted that (1) the conditions reported here for the protonation reaction are not likely to be encountered widely in metathesis systems and (2) the recently discovered formation of methylene complexes from ethylene through a ring-contraction of an unsubstituted tungstacyclopentane to a tungstacyclobutane could be a more general way to make alkylidenes from terminal olefins in the absence of an acid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This work raises the question as to whether nonaryl-substituted terminal olefins behave similarly in terms of protonation or whether styrene is a special case. In terms of the larger picture concerning the formation of alkylidene complexes from olefins, it has to be noted that (1) the conditions reported here for the protonation reaction are not likely to be encountered widely in metathesis systems and (2) the recently discovered formation of methylene complexes from ethylene through a ring-contraction of an unsubstituted tungstacyclopentane to a tungstacyclobutane could be a more general way to make alkylidenes from terminal olefins in the absence of an acid.…”
Section: Discussionmentioning
confidence: 99%
“…Both SSTD and the line shape analysis give the same activation parameters (ΔH ‡ = 15 ± 1 kcal/mol and ΔS ‡ = −9 ± 4 cal/mol•K) for the interconversion of isomers (see the SI and Figure S36). The SSTD method slightly overestimates the rates obtained from 19 F{ 1 H} peak line shapes (for details, see SI section 3). For the SST method, the major experimental error is introduced in the measurement of the spin−lattice relaxation time (see the SI).…”
Section: Interconversion Of Styrene-complexmentioning
confidence: 99%
See 1 more Smart Citation
“…In the dark at 85 °C, 1@SZO only gives 1 mol C 3 H 6 mol W –1 in this reaction, and without heating but with blue LED irradiation, 1@SZO gives 2 mol C 3 H 6 mol W –1 in this reaction. This set of results is similar to previous results reported by us showing that both light and heat are necessary for the direct conversion of ethylene to propylene …”
Section: Resultsmentioning
confidence: 99%
“…4 Studies of well-defined W(VI)−oxo sites supported on silica showed that reduction with an organosilicon reagent in the presence of ethylene forms a tungstacyclopentane that ring contracts to form active metathesis catalysts; 5 similar ring contraction reactions were recently reported for tungstacyclopentanes in solution 6 or supported on silica. 7 An alternative strategy involves the reaction of a d 0 alkylidene with a partially dehydroxylated silica surface, 8 which results in the formation of catalytically active materials that rival or exceed state-of-the-art homogeneous olefin metathesis catalysts. 9 Essentially all well-defined heterogeneous olefin metathesis catalysts are supported on partially dehydroxylated silica, which behaves as an X-or LX-type ligand with a M−O bond and/or a nearby Si−O−Si coordinated to the metal center.…”
Section: ■ Introductionmentioning
confidence: 99%